Revision of the endemic Taiwanese millipede genus Aponedyopus Verhoeff, 1939, with descriptions of two new species (Diplopoda, Polydesmida, Paradoxosomatidae). Advances in the systematica of Diplopoda III - Chen, Chao-Chun (Pensoft Publishers, 2010)
Abstract. The millipede genus Aponedyopus is endemic to Taiwan and contains three species. All previously described nominal species are considered to represent one species: Aponedyopus montanus Verhoeff, 1939 (the type species), including Aponedyopus reesi (Wang, 1957) and Aponedyopus maculatus Takakuwa, 1942, syn. n. Two further species are described as new: Aponedyopus similis sp. n. and Aponedyopus latilobatus sp. n. The genus is re-diagnosed, all of its three species are keyed, and their distributions mapped.